Correlation between ultrawide-field fluorescence contrast results and white blood cell indexes in diabetic retinopathy - Lili Huang; Lele Li; Min Wang; Dongmei Zhang; Yu Song (BMC Ophthalmology, 2022)
Abstract Background Diabetic retinopathy (DR) is one of the most common microvascular complications of diabetes. DR involves a state of systemic inflammation, and chronic inflammation can promote microvascular and macrovascular diseases in diabetic patients and accelerate disease progression. Ultrawide-field FFA (UWFA) systems are increasingly being used to examine a wider retina. The aim of this study was to explore the correlation between the different manifestations of retinopathy under UWFA and the systemic indicators of white blood cells in patients with diabetic retinopathy. Methods This retrospective study included the hospitalized DR patients in the Department of Ophthalmology and Endocrinology of the Affiliated Hospital 2 of Nantong University between January 2016 and March 2019. This study examined the correlations between the UWFA examination results and glycated hemoglobin (HbA1c), routine blood tests,and the neutrophil-to-lymphocyte ratio of patients with clinically diagnosed DR during hospitalization. Results A total of 115 patients with DR (53 females and 62 males) were included (199 eyes: 102 right eyes and 97 left eyes). UWFA revealed that most eyes (77.4%) had grade 4 microvascular leakage, 52.8% had grade 0 capillary non-perfusion area, 59.3% had grade 0 neovascularization, and 92.0% had grade 0 fibrous proliferative membranes. Microvascular leakage was correlated with the NLR (r = 0.186, P = 0.027). Capillary non-perfusion area was correlated with the monocyte ratio (r = 0.144, P = 0.042) and the eosinophil ratio (r = 0.123, P = 0.044). Neovascularization was correlated to the monocyte ratio (r = 0.324, P = 0.018). Finally, the fibrous proliferative membrane was correlated to the monocyte ratio (r = 0.418, P = 0.002). Only the eosinophil ratio was independently associated with proliferative DR (odds ratio = 1.25, 95% confidence interval: 1.04–1.51, P = 0.018). Conclusion The results of UWFA imaging in patients with DR are correlated with white blood cell population indexes. The eosinophil ratio was independently associated with proliferative DR.